PENGARUH FRAUD HEXAGON TERHADAP FINANCIAL STATEMENT FRAUD (STUDI PADA PERUSAHAAN SEKTOR INFRASTRUKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA) - Maghriza, Zachri; Sutoyo (Lembaga Penerbit Fakultas Ekonomi dan Bisnis Universitas Trisakti, 2025)
Financial reports are the key to a company in order to provide a good reputation for the company. The purpose of making financial reports is to minimize the occurrence of falsification of financial information so that there is a difference of interest between agents and shareholders. This is the basis for fraud. Fraud can appear in various forms, one of which is financial statement fraud or financial statement fraud. Financial statement fraud is an action carried out by employees or company staff intentionally, resulting in misrepresentation of financial statements and the omission of material information in financial statement reporting. In this study, the hexagon theory is used as an assessment that can trigger financial statement fraud. The factors used include pressure, opportunity, rationalization, capability, arrogance and collusion. This study aims to test the effect of fraud hexagon on financial statement fraud in infrastructure sector companies listed on the Indonesia Stock Exchange (IDX) for the period 2021-2023 consecutively. The analysis technique used in this study is the multiple linear regression method. The design of this study is quantitative causality supported by secondary data. The sampling technique used a purposive sampling method that focused on 132 observation data with samples of companies in the infrastructure sector listed on the Indonesia Stock Exchange in 2021-2023. The results of hypothesis testing and multiple linear regression analysis show that collusion has an effect on financial statement fraud. Meanwhile, pressure, opportunity, rationalization, capability and arrogance do not affect financial statement fraud.